Prevalence of Cardiovascular Disease Risk Factors and Dietary Patterns of Football Players of Selected Football Clubs in Ashanti Region of Ghana - Afrifa, Daniel (2018)
A thesis submitted to the Department of Biochemistry and Biotechnology in partial fulfillment of the requirements for the award of a Master of Philosophy Degree in Human Nutrition and Dietetics